Frequency-Dependent Intrinsic Electrophysiological Functional Architecture of the Human Verbal Language Network - Coolen, Tim; Wens, Vincent; Vander Ghinst, Marc; Mary, Alison; Bourguignon, Mathieu; Naeije, Gilles; Peigneux, Philippe; Sadeghi, Niloufar; Goldman, Serge; De Tiège, Xavier (Frontiers in Integrative Neuroscience, 2020)
Functional magnetic resonance imaging (fMRI) allowed the spatial characterization of the resting-state verbal language network (vLN). While other resting-state networks (RSNs) were matched with their electrophysiological equivalents at rest and could be spectrally defined, such correspondence is lacking for the vLN. This magnetoencephalography study aimed at defining the spatio-spectral characteristics of the neuromagnetic intrinsic functional architecture of the vLN. Neuromagnetic activity was recorded at rest in 100 right-handed healthy adults (age range: 18-41 years). Band-limited power envelope correlations were performed within and across frequency bands (θ, α, β and low ) from a seed region placed in the left Broca’s area, using static orthogonalization as leakage correction. K-means clustering was used to segregate spatio-spectral clusters of resting-state functional connectivity (rsFC). Remarkably, unlike other RSNs, within-frequency long-range rsFC from the left Broca’s area was not driven by one main carrying frequency but was characterized by a specific spatio-spectral pattern, segregated along the ventral (predominantly θ and α) and dorsal (β and low- bands) vLN streams. In contrast, spatial patterns of cross-frequency vLN functional integration were spectrally more widespread and involved multiple frequency bands. Moreover, the static intrinsic functional architecture of the neuromagnetic human vLN involved clearly left hemisphere dominant vLN interactions as well as cross-network interactions with the executive control network and postero-medial nodes of the DMN. Overall, this study highlighted the involvement of multiple modes of within and cross-frequency power envelope couplings at the basis of long-range electrophysiological vLN functional integration. As such, it lays the foundation for future works aiming at understanding the pathophysiology of language-related disorders.